Secretome-Based Therapy Promotes Epidermal Thickness Recovery and Follicular Regrowth in Fluconazole-Induced Alopecia in Rats - Ametati, Holy; Prawitasari, Salindri; Habibi (Stem Cell and Cancer Research (SCCR), 2025)
Background: Alopecia involves hair loss characterized by decreased follicle density and epidermal thinning, which may be exacerbated by prolonged fluconazole exposure. The secretome derived from human umbilical cord mesenchymal stem cells (hUC-MSCs) possesses anti-inflammatory and regenerative properties that could aid follicular repair. Methods: Twenty-four male Wistar rats were randomly assigned to four groups: control, 5% minoxidil, hUC-MSC secretome, and secretome–minoxidil combination. Alopecia was induced by fluconazole administration for seven days, followed by a seven-day treatment period. Histological evaluation using hematoxylin and eosin staining assessed hair follicle count and epidermal thickness. Results: The hUC-MSC secretome group exhibited a significant increase in follicle count (mean 39.2; p < 0.001) compared with the control and minoxidil groups. However, changes in epidermal thickness were not statistically significant (p = 0.133). Conclusion: hUC-MSC secretome effectively enhances follicular regeneration in fluconazole-induced alopecia and represents a promising biotherapeutic approach for hair restoration.